European Union Policy-Making on Robotics and Artificial Intelligence: Selected Issues - Thomas Kirchberger (Croatian Yearbook of European Law and Policy, 2017)
This article uses the recently issued report on civil law rules on robotics by the European Parliament's Committee on Legal Affairs as an anchoring point. After a brief overview of the topic’s socio-economical background, it contains an attempt to define and explain artificial intelligence. By examining the role of autonomous machines in the workforce, it gives an overview of the most pressing questions the future of labour might bring. One closely connected issue is the still unanswered question of liability regarding artificially intelligent robots, which will most certainly have to be tackled by future policy makers. Another such open question is a new approach on creativity, where the key phrase "own intellectual creation" might have to be redefined in order to cover copyrightable works produced by computers. Lastly, the European Parliament’s Report on Robotics calls for a new European Agency for Robotics and Artificial Intelligence is addressed.